A bibliometric review of 35 years of studies about preeclampsia - Akbari, Razieh; Hantoushzadeh, Sedigheh; Panahi, Zahra; Bahonar, Sajedeh; Ghaemi, Marjan (Frontiers in Physiology, 2023)
The purpose of this study is to investigate preeclampsia. It used the visualization tools of CiteSpace, VOSviewer, Gunnmap, Bibliometrix®, and Carrot2 to analyze 3,754 preeclampsia studies from 1985 to 2020 in Obstetrics and Gynecology areas. Carrot2 was used to explain each cluster in extra detail. The results found that there is an increasing trend in many publications related to preeclampsia from 1985 to 2020. The number of studies on preeclampsia has increased significantly in the last century. Analysis of the keywords found a strong relationship with preeclampsia concepts and keywords classified into five categories. Co-citation analysis was also performed which was classified into six categories. Reading the articles offers important to support not only to grind the context of preeclampsia challenges but also to design a new trend in this field. The number of studies on preeclampsia has substantially improved over the decades ago. The findings of documents published from 1985 to 2020 showed three stages in research on this subject: 1985 to 1997 (a seeding stage), 1997–2005 (rapid growth stage), and 2005 onwards (development stage).